In Memoriam doctor Juan Leónidas Tarazona Barboza (1952-2015) - Romero, Leonardo (2015)
Juan Tarazona, was born on January 28, 1952. I had the honor of to be spectator of part of his academic career, since I was his student and assistant until we were colleague. On May 14, 2015 died Dr. Juan Leonids Tarazona Barboza, an unexpected departure, because the image that always prodigal Professor Tarazona was that of a young restless, eager to undertake research and meet the academic challenges of linking science to society and always I remember like that. In these speach, as a spectator I feel able to describe only a part of his academic career, only the facets that I could see only the short time that I could learn from him and collaborate in their research.